Kemampuan Pemahaman Konsep Guru Mata Pelajaran Tingkat SD dan SMP Pada Workshop Pengembangkan Butir Higher Order Tinking Skills - Wardani Rahayu; Erwin Sulaeman; Yunika Apriyani; Lisa Dwi Ningtyas; Candra Irawan; Mochamad Herlan; Asep Sutisna; Kacep Muslim; Ema Noviah (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
Abstract Higher Order Thinking Skills (HOTS) based learning aims to improve students' critical thinking skills and creative thinking skills. Teachers need to prepare integrated HOTS questions in learning. The ability to develop HOTS items is one of the abilities that teachers must-have. This study aims to develop teacher competence in compiling HOTS items for classroom learning. This activity is in the form of a workshop in the context of implementing Community Service for elementary and junior high school teachers in the DKI Jakarta area. The workshop participants were 146 teachers (Biology, Physics, Chemistry, and Mathematics). The ability to understand workshop material is carried out in self-assessment. The results of the self-assessment of the workshop participants showed that there was an increase in the ability of workshop participants to compile HOTS questions using real problems and to understand the development of open-ended questions from closed questions after the provision of material by the resource person and the practice of writing questions. Abstrak Pembelajaran berbasis Higher Order Thinking Skills (HOTS) bertujuan untuk meningkatkan kemampuan berpikir kritis dan kemampuan berpikir keratif siswa. Guru perlu menyiapkan soal-soal HOTS terintegarsi dalam pembelajaran. Kemampuan pengembangan butir soal HOTS merupakan salah satu kemampuan yang harus dimiliki oleh guru. Tujuan dari penulisan artikel ini untuk mengembangkan kompetensi guru dalam menyusun butir HOTS untuk pembelajaran di kelas. Kegiatan ini berupa workshop dalam rangka pelaksanaan Pengabdian Pada Masyarakat untuk guru SD dan guru SMP di wilayah DKI Jakarta. Peserta workshop sebanyak 146 orang guru (Biologi, Fisika, Kimia, dan Matematika). Kemampuan pemahaman materi workshop dilakukan dalam penilaian self assesment. Hasil self-assessment dari peserta workshop menunjukkan ada peningkatan kemampuan peserta workshop dalam menyusun soal HOTS dengan menggunakan masalah nyata, dan memahami pengembangan soal berbentuk open-ended dari soal berbentuk tertutup setelah pemberian materi oleh narasumber dan praktik penulisan butir soal.